Unemployment in the Great Recession - Pissarides, Christopher A. (London, 2013)
"This paper studies the responses of unemployment in Germany, the United States and Britain to the Great Recession of 2008-09 by making use of Beveridge curve analysis, and in the entire OECD with other techniques. It is shown that Britain suffered from recession but no structural problems; the United States suffered from structural unemployment during the recovery; Germany exhibited a much better performance both during and after the recession. The rise in OECD unemployment is broken down into parts due to aggregate activity, the construction sector and a residual attributed to policies and institutions, which is used to reach conclusions about policy."